Life History Parameters of the Invasive Cotton Mealybug Phenacoccus solenopsis on Tomato at Four Constant Temperatures - Ahlem Harbi; Khaled Abbes; Brahim Chermiti; Pompeo Suma (Insects)
The cotton mealybug, Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae), is an invasive polyphagous pest that has been reported in several tomato-producing Mediterranean countries. However, information regarding the impact of temperature variations on its potential damage and population dynamics on this crop is limited. The effect of four temperatures (20 ± 1 °C, 25 ± 1 °C, 30 ± 1 °C and 35 ± 1 °C) on the development, reproduction, and population growth parameters of P. solenopsis on tomatoes under controlled laboratory conditions was investigated using age-stage two-sex life tables. The increase in temperature caused a significant decrease in the developmental periods of all instars except eggs. The shortest durations of the life cycle (29.58 ± 0.28 days for females and 13.91 ± 0.25 days for males), the adult preoviposition period (APOP), and the total preoviposition period (TPOP) (APOP: 7.78 ± 0.09 days and TPOP: 18.33 ± 0.13 days) were obtained at 35 ± 1 °C. Fecundity varied with temperature, and the highest value was recorded at 30 ± 1 °C (183.29 ± 7.13 eggs/female). The highest average net reproduction rate (R0) (154.24 ± 14.681 offspring/female), intrinsic rate of increase (r) (0.222 ± 0.0036 d−1), and finite rate of increase (λ) (1.248 ± 0.00495 d−1) were observed at 35 ± 1 °C. A simulation of population increase and structure under different temperatures over a period of 90 days revealed that the greatest expected population size was at 35 ± 1 °C, with the completion of four overlapping generations. The data from this study provide valuable information for adapted pest management approaches against P. solenopsis on tomato crops.